Actinic keratosis in the en‐face and slice imaging mode of high‐definition optical coherence tomography and comparison with histology. (5th October 2012) - Maier, T.; Braun‐Falco, M.; Laubender, R.P.; Ruzicka, T.; Berking, C.
Summary Background Optical coherence tomography (OCT) allows real‐time, in vivo examination of nonmelanoma skin cancer. An innovative high‐definition (HD)‐OCT with a horizontal (en‐face) and vertical (slice) imaging mode offers additional information in the diagnosis of actinic keratosis (AK) and may potentially replace invasive diagnostic biopsies. Objectives To define the characteristic morphological features of AK by using HD‐OCT in the two imaging modes compared with histopathology as gold standard. Methods In total, 20 AKs were examined by HD‐OCT in the en‐face and slice imaging modes and characteristic features were described and evaluated in comparison with the histopathological findings. Furthermore, the HD‐OCT images of a subgroup of AKs were compared with those of the clinically normal adjacent skin. Results The preoperative in vivo diagnostics showed the following features in the en‐face imaging mode of HD‐OCT: disruption of stratum corneum, architectural disarray, cellular/nuclear polymorphism in the stratum granulosum/stratum spinosum, and bright irregular bundles in the superficial dermis. In the vertical slice imaging mode the following characteristics were found: irregular entrance signal, destruction of layering, white streaks and dots, and grey areas. In contrast, the clinically healthy adjacent skin showed mainly a regular epidermal 'honeycomb' pattern in the en‐face mode and distinct layering of the skin in the slice mode. Conclusions HD‐OCT with both the en‐face and slice imaging modes offers additional information in the diagnosis of AK compared with conventional OCT and might enhance the possibility of the noninvasive diagnosis of AK prior to treatment procedures and possibly in the monitoring of noninvasive treatment strategies.